Regulation of miRNA expression by α4β1 integrin‐dependent multiple myeloma cell adhesion - Yaiza Rodríguez‐García; Mónica Martínez‐Moreno; Lola Alonso; Anna Sánchez‐Vencells; Alicia Arranz; Roger Dagà‐Millán; Silvia Sevilla‐Movilla; Antonio Valeri; Joaquin Martínez‐López; Joaquin Teixidó (eJHaem, 2023)
Abstract The α4β1 integrin regulates the trafficking of multiple myeloma (MM) cells and contributes to MM disease progression. MicroRNAs (miRNAs) can have both tumor suppressor and oncogenic roles and thus are key controllers of tumor evolution, and have been associated with different phases of MM pathogenesis. Using small RNAseq analysis, we show here that α4β1‐dependent MM cell adhesion regulates the expression of forty different miRNAs, therefore expanding our current view of the α4β1 involvement in MM cell biology. Specific upregulation of miR‐324‐5p and miR‐331‐3p in cells attached to α4β1 ligands was confirmed upon silencing the α4 integrin subunit, and their increased levels found to be dependent on Erk1/2‐ and PI3K‐Akt‐, but not Src‐dependent signaling. Enhanced miR‐324‐5p expression upon α4β1‐mediated MM cell adhesion aimed the hedgehog (Hh) component SMO, revealing that the miR‐324‐5p‐SMO module represents a α4β1‐regulated pathway that could control Hh‐dependent cellular responses in myeloma. Our results open new therapy research avenues around the α4β1 contribution to MM progression that deserve to be investigated.